Median nerve penetration by a persistent median artery and vein mimicking carpal tunnel syndrome. Issue 3 (29th December 2015) - Stavros, Kara; Paik, David; Motiwala, Rajeev; Weinberger, Jesse; Zhou, Lan; Shin, Susan
ABSTRACT: Introduction : Carpal tunnel syndrome (CTS) is a common clinical syndrome seen in the outpatient setting that is easily confirmed by electrodiagnostic testing. Methods : We describe the case of a patient who presented with the classic symptoms and neurological examination for CTS, but had a normal nerve conduction study and electromyogram. Results : Neuromuscular ultrasound of the median nerve on the symptomatic side revealed penetration of the nerve by a persistent median artery and vein in the mid‐forearm, with a positive sonographic Tinel sign over this spot. This finding is an anatomical variation that has been described sparingly in the literature, mostly in cadavers. It has not been reported previously to be a mimic of CTS. Conclusions : This case demonstrates the diagnostic utility of neuromuscular ultrasound and the importance of considering an anatomical variation involving the median nerve in the differential diagnosis of CTS. Muscle Nerve 53: 485–487, 2016